2019
DOI: 10.1007/s10865-019-00122-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and neighborhood factors associated with urban women’s preventive care use

Abstract: Women are more likely than men to forego care-including preventive care. Understanding which factors influence women's preventive care use has the potential to improve health. The focus of this study is the largely understudied areas of psychological barriers (depression) and neighborhood factors (support and stressors) that may be associated with women's preventive care use through secondary analysis of the Chicago Community Adult Health Study. Across models, 30-40% of the variance in preventive care adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 101 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…For instance, the first pandemic surge resulted in a decline in hospitalization rates and lengths of hospital stay associated with acute cardiovascular conditions as well as other common conditions, such as acute appendicitis, bone fractures, cancer, and live births. Given the evidence on differences based on sex [ 40 ], race and ethnicity [ 41 ], sexual and gender identity [ 42 , 43 ], and other key factors, we need to investigate sociodemographic differences in delayed or interrupted care. Further, the significant economic effects of the COVID-19 pandemic as well as the high rates of job loss may result in the loss of insurance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the first pandemic surge resulted in a decline in hospitalization rates and lengths of hospital stay associated with acute cardiovascular conditions as well as other common conditions, such as acute appendicitis, bone fractures, cancer, and live births. Given the evidence on differences based on sex [ 40 ], race and ethnicity [ 41 ], sexual and gender identity [ 42 , 43 ], and other key factors, we need to investigate sociodemographic differences in delayed or interrupted care. Further, the significant economic effects of the COVID-19 pandemic as well as the high rates of job loss may result in the loss of insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, community socioeconomic deprivation is theorized to pose barriers to preventive care, such as diabetes screening, through a range of potential pathways, including poor access to transportation services, lack of social networks that share health information, and shared medical mistrust ( Benkert et al, 2019 ; Veldius et al, 2020 ). Consistent with this hypothesis, we did not observe an association of community socioeconomic deprivation with hyperfiltration at the time of type 2 diabetes detection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GFR at time of type 2 diabetes diagnosis could vary depending upon when during the course of disease an individual is diagnosed. Hyperglycemia may go undetected for a longer time among individuals living in socioeconomically deprived communities due to poor transportation access; lack of social support that encourages utilization of preventive health services (e.g., screenings); and lack of social networks that exchange health information ( Fernandes et al, 2015 ; Veldhius et al, 2020 ). Little is known regarding the association between community socioeconomic deprivation and type 2 diabetes diagnosis delays.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Furthermore, the Chicago Community Adult Health Study found the women's use of preventive care to be associated with objective and perceived neighborhood support and stressors such as odors, presence of trees, and noise levels. (7) The existing literature motivated this study to examine the impact of the built environment on health and healthcare utilization among women, and particularly, the pregnant population. (8)(9)(10) Levels of prenatal care vary across the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have commonly relied on the subjective perceived measures obtained from interviews and questionnaires. (4,7,18) However, relying on subjective measurements may increase recall bias which occurs when some participants recall the exposure differently than others.…”
Section: Introductionmentioning
confidence: 99%